Current therapeutic status of corticosteroid in human immunodeficiency virus patients with tuberculous meningitis - Mishra, Ajit Kumar; Haque, Shoebul; Sachan, A. K.; Dixit, R. K. (International Journal of Research in Medical Sciences, 2022)
Human immunodeficiency virus (HIV) poses risk for severe manifestation of TB. These may be in the form of pulmonary or extra pulmonary. According to the level of immunosupression there is risk of developing tuberculous meningitis (TBM). HIV alters pathogenesis, clinical features and prognosis throwing diagnostic and therapeutic challenges.